2019
DOI: 10.1177/0300985819859877
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Findings in Captive American Horseshoe Crabs (Limulus polyphemus)

Abstract: Histopathology of 61 captive American horseshoe crabs (HSCs; Limulus polyphemus) is reviewed. HSC organs evaluated histologically included body wall (chitin, epidermis, dermis, and skeletal muscle), hepatopancreas, gut, gonads, book gills, eyes, heart, brain, and coxal gland. In descending order, lesions were most frequently identified in compound eye, body wall, book gills, hepatopancreas, chitinous gut, nonchitinous gut, heart, and brain; lesions were not observed in coxal gland or gonads. Hemocytes (also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Vibrio is commonly found in the microbiomes of aquatic organisms and some species have been identified as pathogens, commensals, and mutualists, yet, an understanding of the relationships between many Vibrio species and their hosts requires further research (Thompson et al, 2016). A histological analysis of Limulus identified several bacterial species associated with pathological conditions including Pseudomonas and Aeromonas (LaDouceur et al, 2019) which also appear to be major constituents of what we suspect is a pathological condition in our study, as well. A more comprehensive view of a core horseshoe crab microbiome awaits cultivation-independent surveys of other horseshoe crab species, and more individuals from different geographic and physicochemical environments (e.g., estuarine and marine).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Vibrio is commonly found in the microbiomes of aquatic organisms and some species have been identified as pathogens, commensals, and mutualists, yet, an understanding of the relationships between many Vibrio species and their hosts requires further research (Thompson et al, 2016). A histological analysis of Limulus identified several bacterial species associated with pathological conditions including Pseudomonas and Aeromonas (LaDouceur et al, 2019) which also appear to be major constituents of what we suspect is a pathological condition in our study, as well. A more comprehensive view of a core horseshoe crab microbiome awaits cultivation-independent surveys of other horseshoe crab species, and more individuals from different geographic and physicochemical environments (e.g., estuarine and marine).…”
Section: Discussionsupporting
confidence: 69%
“…Once the exoskeleton of the horseshoe crab has been breached (or degraded), it would then be susceptible to secondary infections and given that adults do not molt, the damage accumulated is irreparable. Previous studies have associated infections in captive lab horseshoe crab populations with eukaryotic parasites, algae, fungi, and bacteria (commonly Cyanobacteria and Gram-negative bacteria) (Leibovitz and Lewbart 2004, Smith 2006; Braverman et al, 2012, LaDouceur et al, 2019). We hypothesize that the appearance of these lesions could be due to dysbiosis of the horseshoe crab microbiome, resulting in an overall increase in the abundance of chitinolytic bacteria or the appearance of opportunistic pathogens capable of degrading chitin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in direct opposition to a study on cownose rays in touch tanks, which concluded that the transfer of human-associated taxa to the rays was negligible ( Kearns et al, 2017 ). Cultural analyses of hemolymph samples from captive Limulus resulted in the isolation of several bacterial species associated with pathological conditions, including Shewanella putrefaciens (formerly Pseudomonas putrefaciens ) and Aeromonas hydrophila ( Khashe and Janda, 1998 ; LaDouceur et al, 2019 ). We hypothesize that the unclassified species of Pseudomonas and Aeromonas that dominate our tank-acclimated population are involved somehow in the development of the diseased state in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Once the exoskeleton of the horseshoe crab has been breached (or degraded), it would then be susceptible to secondary infections and given that adults do not molt, the damage accumulated is irreparable. Previous studies have associated infections in captive lab horseshoe crab populations with eukaryotic parasites, algae, fungi, and bacteria (commonly Cyanobacteria and Gram-negative bacteria) ( Leibovitz and Lewbart, 2003 ; Smith, 2007 ; Braverman et al, 2012 ; LaDouceur et al, 2019 ). We hypothesize that the appearance of these lesions could be due to shifts in the horseshoe crab microbiome, resulting in an overall increase in the abundance of chitinolytic bacteria or the appearance of opportunistic pathogens capable of degrading chitin.…”
Section: Discussionmentioning
confidence: 99%